2020
DOI: 10.3390/plants9020202
|View full text |Cite
|
Sign up to set email alerts
|

Thymus Citriodorus (Schreb) Botanical Products as Ecofriendly Nematicides with Bio-Fertilizing Properties

Abstract: In recent years, interest has surged in the development of plant extracts into botanical nematicides as ecofriendly plant protection products. Aromatic plants are maybe the most studied category of botanicals used in this direction and the yielding essential oils are obtained on a commodity scale by hydro distillation. Nevertheless, can the bioactivity of aromatic plants always be attributed to the terpenes content? What would it mean for soil microcosms to bear the treatment of an essential oil to cure agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Overall, the highest concentration presented, 2 mg/mL, showed the strongest controlling effect on J2, resulting in no root galls after the J2 were incubated for 48 h and 96 h to NEMguard ® DE. These findings are in line with previous investigations, showing that the nematicidal potential of the NEMguard ® solution (NEMguard ® SC), a different formulation as the one we used for our study against M. incognita , is concentration and time dependent [ 20 , 26 ].…”
Section: Resultssupporting
confidence: 93%
“…Overall, the highest concentration presented, 2 mg/mL, showed the strongest controlling effect on J2, resulting in no root galls after the J2 were incubated for 48 h and 96 h to NEMguard ® DE. These findings are in line with previous investigations, showing that the nematicidal potential of the NEMguard ® solution (NEMguard ® SC), a different formulation as the one we used for our study against M. incognita , is concentration and time dependent [ 20 , 26 ].…”
Section: Resultssupporting
confidence: 93%
“…The enhancement of soil enzymatic activity and total microbial biomass by spearmint essential oil is also reported in [ 14 ]. Recently, a study on the impacts of Thymus citriodorus on soil communities and tomato growth showed that different plant parts had different impacts, suggesting the intervention of specific chemical constituents that were included or not in each plant part, and that soil bacterial biomass increased, whereas fungal biomass did not change in its presence [ 29 ]. In contrast, our findings showed a clear positive impact of mint and rosemary leaves on fungi, particularly at the early stages of the decomposition process.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, spearmint composts [ 26 ] or leaves [ 27 , 28 ] incorporated at different rates in the soil, stimulated the growth of tomato plants remarkably while also suppressing weed emergence, particularly of broadleaved species [ 26 ]. Other aromatic plants such as Thymus citriodorus were also found to exert a beneficial effect on tomato growth while successfully controlling root knot nematodes [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Six plastic bags represented the experimental treatments, 1kg of soil each receiving a nematode inoculation 2500 J2 kg −1 . After appropriate mixing and overnight incubation at room temperature according to Ntalli et al, 2020 [50] the plastic bags were spiked with appropriate amounts of LP and WP to reach the test concentrations of 1, 5, 10, 50, and 100 g kg −1 soil. NEMguard SC (garlic extract by Intrachem) was used as a commercial control at the recommended dose (4 L ha −1 that is 2 µL of formulated product per kg soil or 2 mg of a.i per kg of soil) [51].…”
Section: Soil Amending With S Rebaudiana Leaves Powder (Lp) and Wood Powder (Wp) To Treat Against M Incognita And Subsequent Biofertilizamentioning
confidence: 99%